Reversal of the anticoagulant and anti-hemostatic effect of low molecular weight heparin by direct prothrombin activation - Andrade,S.A. (2012)
Lopap, found in the bristles of Lonomia obliqua caterpillar, is the first exogenous prothrombin activator that shows serine protease-like activity, independent of prothrombinase components and unique lipocalin reported to interfere with hemostasis mechanisms. To assess the action of an exogenous prothrombin activator reversing the anticoagulant and antihemostatic effect induced by low molecular weight heparin (LMWH), male New Zealand rabbits (N = 20, weighing 3.8-4.0 kg) allocated to 4 groups were anticoagulated with 1800 IU/kg LMWH (iv) over 2 min, followed by iv administration of saline (SG) or recombinant Lopap (rLopap) at 1 µg/kg (LG1) or 10 µg/kg (LG10), 10 min after the injection of LMWH, in a blind manner. Control animals (CG) were treated only with saline. The action of rLopap was assessed in terms of activated partial thromboplastin time (aPTT), prothrombin fragment F1+2, fibrinogen, and ear puncture bleeding time (BT) at 5, 10, 15, 17, 20, 30, 40, 60, and 90 min after initiation of LMWH infusion. LG10 animals showed a decrease of aPTT in more than 50% and BT near to normal baseline. The level of prothrombin fragment F1+2 measured by ELISA had a 6-fold increase with rLopap treatment (10 µg/kg) and was inversely proportional to BT in LMWH-treated animals. Thus, Lopap, obtained in recombinant form using E. coli expression system, was useful in antagonizing the effect of LMWH through direct prothrombin activation, which can be a possible strategy for the reversal of bleeding and anticoagulant events.